Burnout and Job Satisfaction Among Counselor Educators. Issue 1 (7th April 2013) - SANGGANJANAVANICH, VARUNEE FAII; BALKIN, RICHARD S.
Abstract : The relationship between burnout and job satisfaction among counselor educators was investigated. A total of 220 full‐time counselor educators participated in this quantitative research study. Emotional exhaustion seemed to be the most significant predictor of burnout among counselor educators. Implications for counselor education and future research are discussed.